Signal transmission in mature mammalian vestibular hair cells - Spaiardi, Paolo; Marcotti, Walter; Masetto, Sergio; Johnson, Stuart L. (Frontiers in Cellular Neuroscience, 2022)
The maintenance of balance and gaze relies on the faithful and rapid signalling of head movements to the brain. In mammals, vestibular organs contain two types of sensory hair cells, type-I and type-II, which convert the head motion-induced movement of their hair bundles into a graded receptor potential that drives action potential activity in their afferent fibres. While signal transmission in both hair cell types involves Ca2+-dependent quantal release of glutamate at ribbon synapses, type-I cells appear to also exhibit a non-quantal mechanism that is believed to increase transmission speed. However, the reliance of mature type-I hair cells on non-quantal transmission remains unknown. Here we investigated synaptic transmission in mammalian utricular hair cells using patch-clamp recording of Ca2+ currents and changes in membrane capacitance (ΔCm). We found that mature type-II hair cells showed robust exocytosis with a high-order dependence on Ca2+ entry. By contrast, exocytosis was approximately ten times smaller in type-I hair cells. Synaptic vesicle exocytosis was largely absent in mature vestibular hair cells of CaV1.3 (CaV1.3-/-) and otoferlin (Otof-/-) knockout mice. Even though Ca2+-dependent exocytosis was small in type-I hair cells of wild-type mice, or absent in CaV1.3-/- and Otof-/- mice, these cells were able to drive action potential activity in the postsynaptic calyces. This supports a functional role for non-quantal synaptic transmission in type-I cells. The large vesicle pools in type-II cells would facilitate sustained transmission of tonic or low-frequency signals. In type-I cells, the restricted vesicle pool size, together with a rapid non-quantal mechanism, could allow them to sustain high-frequency phasic signal transmission at their specialised large calyceal synapses.